VALIDATION OF THE FOOTWEAR STAKEHOLDER CHAIN MARKETPLACE (FSCM) IDEA TO INCREASE THE COMPETITIVENESS OF THE FOOTWEAR INDUSTRY - David Sukardi Kodrat; Iswati Iswati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The purpose of this study is to validate an efficient and effective of the footwear stakeholder chain marketplace system for coordination among stakeholders in the footwear industry. Informants used to collect data are suppliers of raw materials, auxiliary materials and machinery in the footwear industry, footwear manufacturers, footwear customers, financial institutions, and logistics services. Methods of data collection using interviews, questionnaires and observation. The data collected is tabulated for the process of analysis, synthesis, and product development using the beta version of the product. The results of the study show the features of consumers, features of manufacturers, features of suppliers, features of funding institutions, and features of validated logistics services. The validated model is beneficial for consumers, suppliers, manufacturers, funding institutions, and logistics services. For consumers, especially can make their own designs. For suppliers and manufacturers, they can share access. For funding institutions and logistics services, they can be very competitive. The creation of this efficiency and effectiveness encourages the development of competitiveness in the footwear industry. Keywords: Stakeholder chain marketplace, efficient, effective, competitiveness, footwear